GEOVACUI-2: Citizen science and cooperative initiatives against depopulation in rural areas : Research note - Mínguez García, Carmen (Geographicalia, 2023)
The decline that characterises the demographic dynamics of many rural areas in Spain justifies the need to analyse the factors that trigger it in order to draw up proposals aimed at resolving them. In the Citizen Science projects GEOVACUI 1 and 2, a participatory approach based on the collection of information from direct testimonies of the actors living in and from the rural environment is used. The participatory tools implemented with the aim of constituting a channel for the expression of ideas have made it possible, on the one hand, to identify differentiated discourses on the productive potential of areas with critical demographic situations (GEOVACUI 1). And on the other hand, to build a repository of geolocalised information on initiatives with a positive impact on rural areas in terms of economic and social dynamisation (GEOVACUI 2). These results, in addition to those derived from the development of seminars with social agents, politicians and citizens of the rural environment, materialised in a proposal of recommendations of various kinds - thematic and territorial - for tackling the phenomenon of depopulation.
Keywords: Depopulation; citizen science; collaborative mapping; Geographic Information Systems